The Effect of the G20 Summit in Bali on Creative Economy and Tourism: Economic Impact Analysis of High-Level Events - Khairune Nisa, An Nuur (Ann Publisher, 2023)
This research examines the impact of the G20 Summit in Indonesia in 2022 on the country's economy, especially in the creative economy and tourism sectors. The G20 summit in Bali became a platform for multilateral collaboration between 19 major economies and the European Union. The main focus of the conference is on issues of global economy and sustainable development with the theme